The application of fat emulsions for the treatment of poisoning and evaluation of they safety in the light of the guidelines of the European Resuscitation Council 2021 - Michał Mazuchowski (Polish Pharmaceutical Society, 2021)
The main application of intravenous lipid emulsions (ILE) is parenteral nutrition. However, in the literature data we can find many indications for the supply of ILE in case of poisoning, which was reflected in the guidelines of the European Resuscitation Council 2021. The most frequently presented mechanism of ILE action in poisoning is the model referred to as "lipid sink" ("fat absorber" or "sponge-in-sink effect"), which involves passing highly lipophilic toxic substances from tissues into the blood and dissolving them in a new intravascular compartment created by ILE. ILE are the treatment of choice in case of poisoning with local anesthetics with well-documented effects. ILE can bring therapeutic benefits in case of poisoning: tricyclic antidepressants, beta-blockers, calcium channel blockers and other drugs when other previous treatments have failed. When cardiac arrest in the course of poisoning is diagnosed, advanced resuscitation procedures combined with high-quality chest compressions should be implemented as soon as possible according to the standard protocol of the European Resuscitation Council, followed by the treatment of choice, specific for the poison. If this does not work, consider the administration of ILE for lipophilic substances where administration of ILE may be of therapeutic benefit. The dosage of ILE in cardiac arrest in poisoning includes a bolus of 1.5 ml of 20% ILE / kg b.w. within 1-2 minutes, followed by a continuous infusion at a rate of 0.25 ml of 20% ILE / kg b.w. / min for 10-60 minutes, until the maximum dose is 12 ml / kg b.w. If necessary, the bolus can be repeated after 5 minutes, and the continuous infusion can be increased to 0.50 ml of 20% ILE / kg b.w. / min. ILE should be available in all places where large doses of local anesthetics are used and in the hospital emergency department due to the possibility of admitting a poisoned patient. Consultation with a poison control center prior to administration of ILE is indicated but not required.